How Smart Firms Power Global Knowledge Acquisitions Through Socialization Mechanisms: Evidence from Malaysian Foreign Subsidiaries - Khaled Shukran; Mohammad Nazri bin Mohamad Nor; Norizah Binti Mustamil (International Journal of Business and Social Science Research, 2023)
This concept paper extends research on knowledge transfer based on the network and resource base. It claims smart firms can accelerate their stock of strategic knowledge by employing an efficient socialization process and gaining competitive advantages. Nonetheless, exploiting the knowledge in the corporate network is not straightforward. The transition of substantial strategic resources within a business must be acquired and used efficiently. Using the socialization process thus significantly reduces the barriers to best practices or strategic knowledge transfer. This paper presents a theoretical model explaining acquiring knowledge through socialization. Nevertheless, this paper demonstrates that without socialization mechanisms, subsidiary-headquarters embeddedness could adversely affect.